2015
DOI: 10.7554/elife.08298
|View full text |Cite
|
Sign up to set email alerts
|

Starvation promotes concerted modulation of appetitive olfactory behavior via parallel neuromodulatory circuits

Abstract: The internal state of an organism influences its perception of attractive or aversive stimuli and thus promotes adaptive behaviors that increase its likelihood of survival. The mechanisms underlying these perceptual shifts are critical to our understanding of how neural circuits support animal cognition and behavior. Starved flies exhibit enhanced sensitivity to attractive odors and reduced sensitivity to aversive odors. Here, we show that a functional remodeling of the olfactory map is mediated by two paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
201
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(216 citation statements)
references
References 64 publications
(108 reference statements)
7
201
0
Order By: Relevance
“…Our results suggest that 5-HT may affect TKK mediated gain control differently relative to processes undertaken by other LN populations. Furthermore, the expression of the TKK receptor by ORNs is regulated by hunger, allowing the effects of TKK to vary with behavioral state67. It would be interesting to determine if the expression of 5-HTRs themselves also vary with behavioral state as a means of regulating neuromodulation within the olfactory system.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that 5-HT may affect TKK mediated gain control differently relative to processes undertaken by other LN populations. Furthermore, the expression of the TKK receptor by ORNs is regulated by hunger, allowing the effects of TKK to vary with behavioral state67. It would be interesting to determine if the expression of 5-HTRs themselves also vary with behavioral state as a means of regulating neuromodulation within the olfactory system.…”
Section: Discussionmentioning
confidence: 99%
“…Two-photon microscopy revealed that the aversive DM5 glomerulus, which is required for aversion to high concentrations of vinegar (Semmelhack and Wang 2009), became reduced in sensitivity and required higher concentrations of vinegar to become active in starved flies than in fed flies. This modulation co-occurred with the effect of starvation-induced increases of short neuropeptide F (sNPF) signaling in the innately attractive DM1 glomerulus (Ko et al 2015; Root et al 2011). This suggests a dual mechanism for starvation-dependent reduction in aversion.…”
Section: Effects Of Internal State On Aversionmentioning
confidence: 92%
“…Another example of starvation increasing tolerance for aversive odors is the role of tachykinin (DTK) in suppressing the activity of the DM5 glomerulus in D. melanogaster (Ko et al 2015). Knocking down DTK reduced attraction to medium concentrations of apple cider vinegar in starved flies, but not fed flies.…”
Section: Effects Of Internal State On Aversionmentioning
confidence: 99%
“…Previous reports showed that endocrine secretions can tune chemosensory system in Drosophila (Ko et al, 2015;Root et al, 2011). However, these responses could differ strongly in social insects.…”
Section: Introductionmentioning
confidence: 98%